2021
DOI: 10.1002/aenm.202003796
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Validated Machine Learning Study of Graphdiyne‐Based Dual Atomic Catalyst

Abstract: Although the atomic catalyst has attracted intensive attention in the past few years, the current progress of this field is still limited to a single atomic catalyst (SAC). With very few successful cases of dual atomic catalysts (DACs), the most challenging part of experimental synthesis still lies in two main directions: the thermodynamic stability of the synthesis and the optimal combination of metals. To address such challenges, comprehensive theoretical investigations on graphdiyne (GDY)‐based DAC are prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 39 publications
0
58
0
Order By: Relevance
“…Depending on our previous work, we continued to develop the use of Gaussian Process regression (GPR) due to its relatively low computation cost on smaller data sets [ 44 ] and previous success at giving promising results on our target dataset. [ 30 ] Our previous work has confirmed that machine learning is an effective tool to predict the thermodynamic stability and electronic structures of GDY‐based electronic structures. To evaluate the influences of introducing p orbitals, we have also introduced the GPR algorithm method to predict both the energetic trend and electronic structures of GDY‐DAC in this work.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Depending on our previous work, we continued to develop the use of Gaussian Process regression (GPR) due to its relatively low computation cost on smaller data sets [ 44 ] and previous success at giving promising results on our target dataset. [ 30 ] Our previous work has confirmed that machine learning is an effective tool to predict the thermodynamic stability and electronic structures of GDY‐based electronic structures. To evaluate the influences of introducing p orbitals, we have also introduced the GPR algorithm method to predict both the energetic trend and electronic structures of GDY‐DAC in this work.…”
Section: Resultsmentioning
confidence: 86%
“…Meanwhile, there were three possible anchoring sites in each unit of GDY based on the previous works. [ 16–18,30 ] The two different elements were placed between the C2 and C3 sites of the alkyl chain in GDY, which were proved to be the most stable position. To guarantee full relaxations, 15 Å vacuum space was introduced in the z ‐direction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an emerging 2D carbon‐network material, graphdiyne (GDY) has attracted great attention from theory to experiment, because of possessing natural semiconductor band gap and superior electrical properties, differing from carbon nanotube and graphene [1–3] . GDY has a planar and conjugate structure with homogeneous nanopores, resulting from the benzene ring and the butadiyne linkage, [4–8] which are composed of sp and sp 2 carbon atoms [9–10] . Graphdiyne has been reported for promising practical applications in catalysis, [11] electrics, [12] detection, [13] energy storage [14] and biomedicine [15] .…”
Section: Figurementioning
confidence: 99%
“…In contrast, Ni/Fe DMS structure with adsorbed CO reduces the barrier for *COOH formation and the *CO desorption simultaneously, which extremely promotes CO formation (Figure 8I). Huang et al 160 used the DFT and machine learning techniques to propose the Ln–transition metal (TM) DMS systems as the promising electrocatalyst candidates with expected high electroactivity and durability in the long‐term applications. They further experimented with verifying that a Zn/Ln DMS catalyst was highly effective for ECR to produce CO/H 2 syngas with a tunable ratio 159 .…”
Section: Strategies For Optimization Of Ldm Supported Sacs For Ecrmentioning
confidence: 99%